PEMBERDAYAAN MASYARAKAT MELALUI PENYULUHAN PERILAKU HIDUP BERSIH DAN SEHAT UNTUK MENINGKATKAN KUALITAS KESEHATAN MASYARAKAT DI KECAMATAN MEDAN LABUHAN - Fahra Dilla Sandy Sipayung; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
This study intends to research community empowerment through PHBS with GERMAS in advance the health quality of the community. The study design used was a literature study with secondary evidence collection and analysis. The data used is obtained from various document sources and related literature. In this research, it was found that PHBS and GERMAS are effective approaches to prevent diseases, improve individual health, and create a better life in society. Community empowerment is carried out through health education, education on healthy living behaviors, environmental improvement, disease prevention, nutrition fulfillment, and physical activity. This movement involves active community participation, cross-sector cooperation, supervision, evaluation, and policy support